Socio-Sufism of Orang Maiyah: Toward Human Sovereignity in Togetherness - Rizqa Ahmadi (Graduate Program of Pontianak Institute of Islamic Studies, 2017)
Among various religious groups in Indonesia is Orang Maiyah (Gathering Community) that has become a unique phenomenon. Cak Nun (Emha Ainun Najib) is the central figure in the community as well as the source of knowledge and inspiration for its members (although in so many occasion Cak Nun refuses to be called so). This paper explores the style of social Sufism teachings attached to the community approached by descriptive qualitative analysis. This work shows that Orang Maiyah, which is spread in various regions of Indonesia, has become a religiously motivated movement that brings people together to achieve a